The effect of variable viscosity in double diffusion problem of MHD from a porous boundary with Internal Heat Generation. (20th December 2010) - Ferdows, M.; Bangalee, M.Z.I.; Crepeau, J.C.; Seddeek, M.A.
The steady, laminar boundary layer, two-dimensional Magnetohydrodynamics (MHD) flow past a continuously moving (with constant velocity) semi-infinite vertical porous plate is studied taking into account the Dufour and Soret effects (Double diffusion) on variation of fluid viscosity with temperature. The effect of an exponential form of Internal Heat Generation (IHG) is also considered. The fluid viscosity is assumed to vary as a linear function of temperature. The governing fundamental equations of the problem are obtained by using the usual similarity technique. The local similarity solutions of the transformed dimensionless equations are solved numerically. The effects of the governing parameters within the boundary layer of the flow field are studied and the corresponding set of numerical results for the non-dimensional velocity, temperature and concentration profiles as well as the skin friction parameter, Nusselt number and Sherwood number are illustrated and displayed with the aid of graphs and tables to show typical trends of the solutions considering with and without IHG. It has been found that the results of the present study are completely different from similar problems in the absence of double diffusion and IHG.